Calcium is an essential cofactor for metal efflux by the ferroportin transporter family - Deshpande, Chandrika N. (Nat Commun, 2018)
Ferroportin (Fpn)—the only known cellular iron exporter—transports dietary and recycled iron into the blood plasma, and transfers iron across the placenta. Despite its central role in iron metabolism, our molecular understanding of Fpn-mediated iron efflux remains incomplete. Here, we report that Ca(2+) is required for human Fpn transport activity. Whereas iron efflux is stimulated by extracellular Ca(2+) in the physiological range, Ca(2+) is not transported. We determine the crystal structure of a Ca(2+)-bound BbFpn, a prokaryotic orthologue, and find that Ca(2+) is a cofactor that facilitates a conformational change critical to the transport cycle. We also identify a substrate pocket accommodating a divalent transition metal complexed with a chelator. These findings support a model of iron export by Fpn and suggest a link between plasma calcium and iron homeostasis.